2013
DOI: 10.1038/jcbfm.2013.14
|View full text |Cite
|
Sign up to set email alerts
|

An MRI-Histological Study of White Matter in Stroke-Free SHRSP

Abstract: Hypertension is associated with cerebral small vessel disease (SVD) and with diffuse white matter hyperintensities (WMH) on T2-weighted magnetic resonance imaging (MRI). We tested whether stroke-prone spontaneously hypertensive rats (SHRSP), a model of chronic hypertension, exhibit WMH. Male SHRSP (age 10 months) without stroke symptoms were compared with age-matched male WKY rats. Stroke-prone spontaneously hypertensive rats exhibited no WMH on MRI scans (T2, T2*, diffusion tensor imaging) and no neuropatholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 26 publications
3
32
1
Order By: Relevance
“…Despite the significant increase in BP there was no significant correlation between these indices and the observed alterations in FA. Our data are in agreement with others who recently identified no overt disruption in the WM of SHRSP rats, who survived stroke free up to ten months 10 or required the addition of chronic hypoperfusion to elicit WMLs. 14 Taken together the data suggest that hypertension alone for the duration tested here is insufficient to drive WM alterations and we further show that in aged rats (~21months) the combination of ageing and late onset hypertension does not impact on WM integrity in this model.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Despite the significant increase in BP there was no significant correlation between these indices and the observed alterations in FA. Our data are in agreement with others who recently identified no overt disruption in the WM of SHRSP rats, who survived stroke free up to ten months 10 or required the addition of chronic hypoperfusion to elicit WMLs. 14 Taken together the data suggest that hypertension alone for the duration tested here is insufficient to drive WM alterations and we further show that in aged rats (~21months) the combination of ageing and late onset hypertension does not impact on WM integrity in this model.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with recent data indicating that SHRSP that survive into old age without developing stroke, fail to show gross WMLs. 10 Given the discrepancies in the influence of hypertension between the two commonly utilized models, and the difficulty in exploring isolated hypertension in humans because of a multitude of comorbid risk factors including diet, diabetes, and genetic susceptibility, 1,11 we aimed to explore the alterations in WM integrity using MRI and immunohistochemistry in an inducible hypertensive transgenic rat, in which the onset and duration of hypertension are controllable. 12 We have previously demonstrated that MRI is sensitive to subtle WM alterations in a mouse model of modest cerebral hypoperfusion, 13 and as such we hypothesize that sustained hypertension would lead to microstructural alterations in central nervous system WM and further that ageing or additional cerebrovascular risk factors, such as high-fat intake, would exacerbate WM disruption.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence from animal models also suggest that hypertension is not the key driver of white matter changes. 36,37 Our results show that some radiologic, pathologic, and cognitive features of human SVD can be recapitulated in a mouse model by common carotid stenosis. Our findings also provide evidence that hypoperfusion may precipitate SVD-like disease culminating in a progressive brain and gliovascular pathology.…”
Section: Discussionmentioning
confidence: 74%
“…19 Normally, SHR/SP can live up to 9 months without magnetic resonance imaging (MRI) or pathologic evidence of brain damage. 20 We have shown that feeding SHR/SP a diet consisting of low protein and high salt, the Japanese Permissive Diet (JDP), along with unilateral carotid artery occlusion (UCAO), produces an accelerated injury to the WM that is associated with MMP expression, BBB disruption, death of mature oligodendrocytes, and expression of oligodendrocyte precursor cells; the extent of injury can be monitored noninvasively with MRI and the behavioral changes with Morris water maze (MWM). 21 Using an oxygensensitive crystal with electron paramagnetic resonance, we showed an increase in oxygen extraction in the WM at 12 weeks of life with a drastic decrease in oxygen from the thirteenth to the sixteenth week when the animals died.…”
Section: Introductionmentioning
confidence: 99%